Characteristics of the Rhizospheric AMF Community and Nutrient Contents of the Dominant Grasses in Four Microhabitats of the Subalpine Zone in Northwestern Yunnan, China - Li, Wei; Yang, Jiqing; Zhan, Fangdong; Guo, Jiawei; Zhang, Ya; Ba, Yong; Dong, Hengwen; He, Yongmei (Forests, 2024)
At the southeastern periphery of the Tibetan Plateau, the subalpine ecosystem hosts grasses as some of the most substantial species. However, the community and function of arbuscular mycorrhizal fungi (AMF) around the rhizospheres of grasses in the subalpine zone are still poorly understood. In the present study, 28 soils and 11 species of dominant grasses collected from four microhabitats (shrubland, grassland, woodland, and forest) in the subalpine zone of northwestern Yunnan, China, were used to investigate the AMF community by Illumina MiSeq high-throughput sequencing technology as well as nutrient contents. Among the four microhabitats, the maximum soil nutrient levels around the rhizospheres of grasses were observed in woodland. The nitrogen, phosphorus, and potassium concentrations in Dactylis glomerata shoots were significantly higher than those in the other 10 grass species. The AMF diversity of grassland in summer was substantially greater than that of the other three microhabitats (p < 0.05). Discrepancies were observed within a given plant species across microhabitats; for example, in summer, the nitrogen concentration in the shoot of Iris tectorum in woodland was significantly higher than that in both forest and shrubland (p < 0.05). A total of eight genera were detected in the AMF communities, which were dominated by Glomus, with a relative abundance of 45.4%–94.4% in summer and 60.5%–84.3% in winter. Moreover, the abundance of Glomus was significantly positively correlated with the content of alkali-hydrolyzable nitrogen in soil and nitrogen in grasses according to the Mantel test. As a critical nutrient element in soil, nitrogen is beneficial for plant growth. Thus, these results provide a better understanding of the resilience of soil AMF community and the ecological adaptability of grasses in the subalpine ecosystems of northwestern Yunnan.